Pelatihan Membuat Desain Logo Vector Menggunakan Adobe Illustrator dan Adobe Flash di SMK Bina Cipta Palembang - Novan Wijaya (Jurnal Pengabdian Pada Masyarakat, 2016)
Information technology is growing rapidly, especially graphic design which beneficial to the advancement of education. In the science of graphic design can give participants skill to communication visually, either text or images to convey a message. Graphic design skilla are needed in various fields of business such as printing, advertising, multimedia, fashion, industry and education until creative industries. Software used is Adobe Illustrator. Adobe illustrator based on vectors. Final result obtained better than quality if magnification/zoom. Output of this activity is praticipants can implement graphic design either form of making school environment a bulletin board or other announcements can be implemented in the world as well as work related to graphic design.